2017
DOI: 10.1371/journal.pntd.0005582
|View full text |Cite
|
Sign up to set email alerts
|

“We do not bury dead livestock like human beings”: Community behaviors and risk of Rift Valley Fever virus infection in Baringo County, Kenya

Abstract: BackgroundRift Valley Fever (RVF), is a viral zoonotic disease transmitted by Aedes and Culex mosquitoes. In Kenya, its occurrence is associated with increased rains. In Baringo County, RVF was first reported in 2006–2007 resulting in 85 human cases and 5 human deaths, besides livestock losses and livelihood disruptions. This study sought to investigate the county’s current RVF risk status.Methodology and principal findingsA cross-sectional study on the knowledge, attitudes and practices of RVF was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 31 publications
(76 reference statements)
8
41
2
Order By: Relevance
“…A study to assess the impact of zoonotic infections in selected regions of The Gambia, Senegal, Guinea, and Guinea Bissau indicated that cattle with hygroma, which is a typical symptom for brucellosis, are often not considered to be sick and milk is consumed without heat treatment (Unger and Munstermann, 2004). These results were however contrasting to those obtained from the study in Baringo County where majority of the survey respondents (91.5%), reported that they always boiled their milk before consumption and (62.4%) never consumed milk from sick livestock (Mutua et al 2017). Aborted fetuses were disposed of, with unprotected hands and sometimes the herdsmen help some cows having difficulties during calving, without wearing gloves.…”
Section: Awareness Of Zoonoses As Threat To Public Healthcontrasting
confidence: 66%
See 2 more Smart Citations
“…A study to assess the impact of zoonotic infections in selected regions of The Gambia, Senegal, Guinea, and Guinea Bissau indicated that cattle with hygroma, which is a typical symptom for brucellosis, are often not considered to be sick and milk is consumed without heat treatment (Unger and Munstermann, 2004). These results were however contrasting to those obtained from the study in Baringo County where majority of the survey respondents (91.5%), reported that they always boiled their milk before consumption and (62.4%) never consumed milk from sick livestock (Mutua et al 2017). Aborted fetuses were disposed of, with unprotected hands and sometimes the herdsmen help some cows having difficulties during calving, without wearing gloves.…”
Section: Awareness Of Zoonoses As Threat To Public Healthcontrasting
confidence: 66%
“…Conversely, in Kenya 51% of the respondents ate meat from animals which died from sickness (Mutua et al, 2017). This is probably because of the believe that meat from dead or sick animals can be eaten following treatment with Warbugia ugandensis, Acacia tortilis, Acacia nubica, and Myrisine africana leaves and upon boiling with herbs from these tree species as it was the case in Baringo County in Kenya (Mutua et al, 2017). In yet another study carried out in Gambia, Senegal, Guinea, and Guinea Bissau by Unger and Munstermann (2004), it was reported that a majority of participants consume meat from animals infected with brucellosis or tuberculosis after proper cooking or application of traditional treatment.…”
Section: Disposal Of Dead Animalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Distinct agro-ecological profiles of the study areas and/or lifestyles of the population enrolled in the present and previous studies might have also been associated to the differential rates observed. Indeed, it has been suggested elsewhere that the risk of RVFV could vary greatly with respect to the communities and the professions considered [ 14 , 16 , 17 ]. In contrast to RVFV whose exposure rates were comparable among groups, the rate of CCHF IgG was relatively higher among individuals from Abong Mbang compared to those from other studied districts.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological disease such as meningoencephalitis caused by RVFV leads to morbidity and mortality in people during human outbreaks and may pose a challenge for development of effective vaccines and therapeutics (Bird et al, 2012; Scharton et al, 2014). While RVF is a mosquito-transmitted disease, herdsmen, farmers, and other people living in close proximity to livestock or consuming animal products are at increased risk for infection and development of severe forms of RVF disease (Mutua et al, 2017; Nicholas et al, 2014). For individuals handling sick and dying animals, mucosal exposure of the eyes/nose/mouth or inhalation of virus from infected tissues may occur (Anyangu et al, 2010; Madani et al, 2003; Mutua et al, 2017).…”
Section: Introductionmentioning
confidence: 99%